PML, SUMOylation, and Senescence - De Thé, Hugues; Ivanschitz, Lisa; Le Bras, Morgane (Frontiers in Oncology, 2013)
Since its discovery, 25 years ago, PML has been an enigma. Implicated in the oncogenic PML/RARA fusion, forming elusive intranuclear domains, triggering cell death or senescence, controlled by and perhaps controlling SUMOylation... there are multiple PML-related issues. Here we review the reciprocal interactions between PML, senescence and SUMOylation, notably in the context of cellular transformation.